Extraction of physiological parameters to screen potential implantable cardiac defibrillator (ICD) receiver - Tan, Wei Kiat, 1989-, author; Malarvili Balakrishnan; Fakulti Biosains dan Kejuruteraan Perubatan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda Kejuruteraan (Bio - Perubatan)) - Universiti Teknologi Malaysia, 2013